PELATIHAN LITERASI KEUANGAN PADA ERA COVID-19 DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA - Amir Hamzah; Herma Wiharno; Teti Rahmawati; Odang Supriatna (Faculty of Economics and Business YARSI University, Jakarta, Indonesia, 2022)
Community service was carried out on PKK Mother Nurul Huda Awirarangan Village, Subdistrict and Kuningan Regency, West Java. This activity aims to provide knowledge and understanding of financial literacy in the covid-19 era to housewives who are members of the PKK Nurul Huda organization. The training materials provided are about planning, recording about family income and expenditure and simple reporting in the form of bookkeeping, the existence of dissuction and Q&A activities between speakers and participants to make socialization and training conditions run well and actively. This activity was carried out in two places, namely the Multipurpose Building and the Village Meeting Room with a total of about 15 participants and still tried to follow health protocols during the covid-19 pandemic. The results of socialization and training activities participants are able to know and be skilled about family financial management and are expected to be able to be applied in their daily lives. Keywords: Financial Literacy, Financial Management, Family Finance, PKK Nurul Huda